Creature Comforts: Neoliberalism and Preparing for Disaster. Issue 2 (3rd April 2021) - Ray, Emily
ABSTRACT: This article examines the ideological trends in Silicon Valley and how that influences the way Americans prepare for climatic, political, and economic disaster. The suite of ideas called the Dark Enlightenment influence the makers and designers of doomsday preparation products for the middle classes, which in turn folds addressing global instabilities into a neoliberal and anti-democratic project that emphasizes individual consumption over collective action. This article argues that even as human life confronts unprecedented challenges for survival, society organized through neoliberal principles precludes collective democratic processes for addressing an uncertain future.